Massacre at Oradour, France, 1944 : coming to grips with terror - Fouché, Jean-Jacques 1940- (Northern Illinois Univ. Press, 2005)
"Near the end of World War II, four days after Allied armies landed at Normandy, a unit of Waffen SS troops en route to the front surrounded the French village of Oradour-sur-Glane and, without warning, systematically massacred its citizens. The Nazi soldiers herded women and children into the village church, machined-gunned them, and set the church on fire while some were still alive. The men were taken to barns in groups, where they were shot. Afterward, the Nazis plundered the village and burned it to the ground. Altogether, more than 640 French men, women, and children died in Oradour that day." "Jean-Jacques Fouche explores the massacre from several points of view - religious or ethnic differences, the background and training of the Nazi soldiers, and German suspicions that villagers sheltered Jewish and Spanish anti-fascist refugees. Probing the most shocking massacre in World War II France, he shows how memory affects our understanding of the past."--BOOK JACKET.